1996
DOI: 10.1088/0965-0393/4/5/002
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of beryllium diffusion in the base layer of InGaAs/InP heterojunction bipolar transistors

Abstract: To explain the observed beryllium diffusion profiles in the InGaAs base layer of InGaAs/InP heterojunction bipolar transistors, the most basic form of Frank - Turnbull mechanism is proposed and implemented in a computer simulation program. A double profile is obtained which may be explained by the reduction in the vacancy concentration in the bulk of the crystal below its equilibrium concentration. Calculated profiles are computed and compared with our experimental profiles and with other beryllium diffusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Investigations on p-type dopant diffusion in InP based epitaxial compounds, in particular Be in InGaAs, are still limited [1,2,12]. In a previous paper, we found that the diffusion coefficient is time independent under our experimental conditions.…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…Investigations on p-type dopant diffusion in InP based epitaxial compounds, in particular Be in InGaAs, are still limited [1,2,12]. In a previous paper, we found that the diffusion coefficient is time independent under our experimental conditions.…”
Section: Introductionmentioning
confidence: 62%
“…Indeed, only a small but very rapidly diffusing fraction of (c) Be atoms is of interstitial type. Furthermore, there is no real experimental possibility of estimating the C eq i value which mainly depends on epitaxial method and growth parameters [2,12,20]. Consequently, in the initial doped layer, the Be interstitial concentration C eq i was chosen to be about two orders of magnitude lower than C eq s , and it was set at zero in the undoped layers.…”
Section: Theoretical Analyses and Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some questions concerning peculiarities of beryllium diffusion are still unresolved because of the limited experimental data. For example, at an earlier stage of investigations it was believed that the diffusion occurred due to the Frank-Turnbull mechanism that involved a vacancy [6] or due to combination of kick-out and the Frank-Turnbull mechanisms [10]. At the present time a kick-out mechanism due to interaction of group III self-interstitial III I q+ with substitutionally dissolved impurity atom Be -via reaction…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, many efforts were made to investigate experimentally Be diffusion in compound semiconductors [2][3][4][5][6][7][8][9][10][11][12][13][14]. Many efforts also were made to simulate Be diffusion [1,[6][7][8][9][10][11][12][13][14]. However, some questions concerning peculiarities of beryllium diffusion are still unresolved because of the limited experimental data.…”
Section: Introductionmentioning
confidence: 99%